2010
DOI: 10.2478/v10119-010-0015-1
|View full text |Cite
|
Sign up to set email alerts
|

Seed germination in sedges: a short review

Abstract: Five patterns of seed germination in the sedges of the genus Carex are presented, based on the literature data and the results of the authorsí own research. They include the pattern of C. acutiformis, C. arenaria, C. remota, C. flava and C. communis. These patterns were constructed on the basis of seed specific requirements for development, such as stratification, temperature, dormancy and time of germination. Majority of sedges follow the pattern of C. acutiformis or C. remota. In both cases, stratification a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Generally, seed germination is usually inhibited by many environmental factors, such as soil moisture, temperature, and germination time18192021. Seedlings only emerge at the initial recovery growing season, which may be ascribed to the relatively higher soil moisture and temperature in October and November after flooding.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, seed germination is usually inhibited by many environmental factors, such as soil moisture, temperature, and germination time18192021. Seedlings only emerge at the initial recovery growing season, which may be ascribed to the relatively higher soil moisture and temperature in October and November after flooding.…”
Section: Discussionmentioning
confidence: 99%
“…There is a positive correlation between seed mass and germination index, and between seed mass and germination rate. Seeds with larger size have higher germination rate than seeds with smaller size (Maas, 1989;Wu and Du, 2007;Żukowski et al, 2010;Khan et al, 2014). C. cajan seeds of Leguminosae just germinated in M 2 medium, in 3 DAS, with 20% of germination rate until 13 DAS.…”
Section: Germination Rate Among Local Species Seedsmentioning
confidence: 99%
“…On the contrary, we found that light that arrives through small gaps in the canopy and not directly from the sun seems to have a positive effect on C. remota germination. Previous studies ( Brändel and Schütz, 2005 ;Zukowski et al, 2010 ) have shown that sedge germination occurs when there is a very limited range of light and indirectly fl uctuating temperatures ( Albrecht and McCarthy, 2011 ). Germination strategies of forest plants are adapted to use such narrow windows in time ( Brändel and Schütz, 2005 ;ten Brink et al, 2013 ) so continuous censuses of seedlings and related measurements in soil conditions will clear up factors determining establishment processes that are critical for maintaining forest plant populations ( Harper, 1977 ).…”
Section: Discussionmentioning
confidence: 97%
“…For example, in the germination and establishment of herbaceous species, one of these fi lters is the physical barrier imposed by the tree leaf litter ( Facelli and Pickett, 1991 ;Vellend et al, 2000 ). The germination and establishment of forest herbs tend to be strongly sensitive to variations in topography, temperature, and light ( Jacquemyn et al, 2010 ;Laskurain et al, 2004 ;Zukowski et al, 2010 ). In addition, establishment is a phase of the plant life cycle strongly determined by the biotic interactions among seedlings and with adult conspecifi cs ( Leishman, 1999 ;De la Cruz et al, 2008 ).…”
Section: Study Design -mentioning
confidence: 95%